Peranan Media Sosial Dalam Peningkatan Motivasi Belajar Siswa Pada Mata Pelajaran PAI di SMK Miftahul Ulum Bandar Lampung - Maimunah, Siti; Anwar, Muhammad Saidun; Irhamudin, Irhamudin (Jurnal Keislaman, 2025)
The purpose of a study is 1) to analyze the role of social media in increasing students' learning motivation in Islamic religious education subjects at SMK Miftahul Ulum Bandar Lampung, 2) The most effective type of social media in increasing students' learning motivation in Islamic religious education subjects at SMK Miftahul Ulum Bandar Lampung, 3) The challenges of the role of social media in increasing students' learning motivation in Islamic religious education subjects at SMK Miftahul Ulum Bandar Lampung The type of research used by the researcher is qualitative research using descriptive methods, data collection methods in the form of interviews and documentation, data sources via the principal, teachers, and students. The results of the study are as follows: 1) The role of social media is not only communication but also innovation for teachers and students, 2) The types of social media used are Whatsapp, Instagram and Youtube, the researcher uses whatsapp as a type of social media because SMK Miftahul Ulum is more dominant in the use of these social media, 3) The challenge of the role of social media is to distinguish between fake news and valid news, as a teacher it is wiser to provide guidance and wiser in education about the use of social media and the role of teachers must also keep up with the times so as not to be left behind.